Decompression sickness-induced skeletal muscle injury: an animal model and pathological analysis - Chen, Guanghua; Huang, Yongbin; Huang, Chunman; Li, Liwei; Pang, Jingqun; Li, Hongqiang; Zhang, Wenxi (Frontiers in Veterinary Science, 2024)
The primary objective of this investigation is to establish an animal model that accurately represents skeletal muscle injury as a consequence of decompression sickness. Additionally, this study aims to delineate the potential mechanisms underlying the development and progression of skeletal muscle damage associated with decompression sickness. Materials and methods: (1) In this research, rats were utilized as experimental models and subjected to 600 kPa pressure in an air medium for a duration of 60 minutes, followed by decompression at a consistent rate of 1.5 minutes to reach atmospheric pressure in order to establish an animal model for decompression injury. Assessment of decompression injury involved the observation of general symptoms and signs, as well as histopathological examination of lung tissue to determine the extent of damage in the pulmonary system of rats.(2) Building on the rat decompression injury model, we conducted pathological and serological examinations to assess the status of rat skeletal muscle. Additionally, we investigated the signaling mechanism of the TLR9-MyD88 pathway in mediating alterations in rat skeletal muscle resulting from decompression injury, and evaluated the effects of decompression injury on apoptosis in rat skeletal muscle. Results: Repeated decompression induces significant damage to skeletal muscle tissue, characterized by edema, fiber rupture, and atrophy. This process also leads to a transient elevation in creatine kinase (CK-MM) levels in rat serum, as well as an upregulation of proteins such as TLR9, MyD88, p38, and ERK in rat skeletal muscle tissue. Furthermore, repeated decompression results in a temporary increase in the transcription levels of Atrogen-1mRNA and MuRF-1mRNA in rat skeletal muscle tissue. Discussion: The decompression protocol applied in this study successfully induced decompression sickness in a rat model, leading to skeletal muscle damage that was consistent with the expected pathology of decompression injury. Despite the initial injury, the rats showed evidence of adaptation following prolonged exposure to decompression conditions.